A case of synchronous high‐grade cervical intraepithelial neoplasia and metastatic squamous cell carcinomas of unknown primary in rectum. Issue 7 (18th April 2021) - Orisaka, Syunsuke; Nakamura, Mitsuhiro; Obata, Takeshi; Iwadare, Junpei; Mizumoto, Yasunari; Fujiwara, Hiroshi
Abstract: We report a case of synchronous high‐grade cervical intraepithelial neoplasia (CIN) and metastatic squamous cell carcinomas (SCCs) of unknown primary in the rectum. A 74‐year‐old woman was diagnosed with CIN3 by biopsy of the uterine cervix. Magnetic resonance imaging showed two masses in the outer rectal wall. They were diagnosed as SCCs by transrectal biopsy from one mass. On surgical treatment, CIN3 and SCCs in the rectum were identified, respectively. Pathological analysis revealed that SCCs were observed in serosa of the rectum, not mucosa, indicating that these tumors were metastatic SCCs. Gene analysis showed HPV31‐positive and TP53 mutation in CIN3, and HPV16‐positive in rectal SCCs. Pretreatment examination did not detect the primary site of metastatic SCCs in the rectum. We diagnosed the patient with synchronous CIN3 and metastatic SCCs of unknown primary in the rectum. In this case, gene analysis was useful to clarify the relationship between CIN3 and SCCs.